PROPOSED ONLINE MARKETING STRATEGY TO RAISE BRAND AWARENESS FOR VELMARE BY SOCIOLLA - Ananda Budiman, Fadhel; Windasari , Nila Armelia (LPSDI Bina Patria, 2023)
The development of Industry 4.0 has been rapidly progressing worldwide, including in Indonesia. This has led to digitalization in various business industries, from infrastructure to product sales. The COVID-19 pandemic in 2020 further accelerated this transition, as people turned to online platforms for their activities. Velmare, a local Indonesian skincare brand, recognized this opportunity and began selling their products exclusively online through different platforms. However, Velmare has been facing challenges in terms of competitiveness compared to other local skincare brands. Its competitors have adopted an omnichannel strategy, selling products both online and offline. As a result, Velmare needed to develop a new strategy to stay relevant. To determine the potential, strengths, weaknesses, and threats to the Velmare brand, a business analysis was conducted, which involved internal and external assessments. Internal analysis utilized the Marketing Mix (4P), VRIO, and STP analysis, while external analysis involved PESTLE analysis, Porter's Five Forces, and stakeholder analysis. Additionally, a questionnaire was distributed to approximately 160 respondents to assess Consumer-Brand Engagement (CBE) through various points of analysis. The obtained analysis results were processed using SmartPLS software and the SEM-PLS method to measure the correlations between the variables used in the research. The primary objective of this research was to provide business solutions that would enhance purchase intention, brand image, and brand awareness for Velmare. The framework model was analyzed with high accuracy and can serve as a reference for proposing business solutions. The research model framework incorporated variables such as electronic word-of-mouth (EWOM), interaction, trendiness, entertainment, promotion, and omnichannel to achieve consumer-brand engagement. This engagement, in turn, influenced brand image and brand awareness, ultimately determining customer purchase intention. The author hopes that the proposed research objectives will be achieved, thereby addressing the challenges faced by Velmare.